Bulbophyllum lampadion (section Monanthes), a new species from New Guinea - Vermeulen, Jaap J.; Perry, Malcolm; Schuiteman, André (Lankesteriana: International Journal on Orchidology, 2024)
Bulbophyllum lampadion from New Guinea is herein described and illustrated based on herbarium specimens and cultivated material. This high-elevation species belongs to section Monanthes, of which sect. Oxysepala is here considered to be a synonym.